Diversity, Vegetation Structure, Estimated Biomass and Carbon Stock in The Site of Limboto Lake of Gorontalo Regency - Rahim, Sukirman; Baderan, Dewi Wahyuni K; Arfa, Bella Saskia; Angio, Melisnawati H; Hariri, Muhammad Rifqi; Putri, Dwinda Mariska (Bioeksperimen: Jurnal Penelitian Biologi, 2023)
The development of Limboto Lake  Site as the pilot area of Gorontalo Geopark is one step  in rescuing the lake. This research aims to analyzed  the vegetation structure, estimate biomass, and assess the carbon stock value of the vegetatio at the Limboto Lake site. This study employed a purposive sampling method. Important Value Index, a measure used to evaluate plant vegetation structure, was calculated based on Realtive Density, Relative Dominance, and Relative Frequency values. Biomass estimation and carbon stock assessment were conducted using allometric equations. The study’s finding showed that the vegetation surrounding Soekarno's landing area exhibited the highest IVI (sawlogs) scores for Swietenia mahagoni tree at 82.86%, Leucaena leucocephala saplings at 79.56%, and Manihot esculenta seedlings at 46.33%. Leucaena leucocephala consistently achieved the highest IVI score within the Limboto Lake area with a score as high as 76.90%, followed by Leucaena leucocephala on the sapling level with a score as high as 70.03%, and Nauclea orientalis on the seedling level with a score as high as 53.06%. Swietenia mahagoni, Samanea saman, and Leucaena leucocephala are three species with stems that predominate at the sawlog level and sapling, and these stems have high carbon absorption values.